OPTIMASI PENGAMBILAN KEPUTUSAN KOMPENSASI KARYAWAN MENGGUNAKAN METODE TOPSIS: STUDI KASUS PADA PERUSAHAAN XYZ - Stephanie Kartika Nuri Novitasan; Christofani Gracia Retno Palupi; Soetam Rizky Wicaksono (Jurnal Manajemen dan Pemasaran, 2025)
This research aims to develop a decision support system (SPK) in determining employee compensation in Company XYZ using the TOPSIS method (Technique for Order Preference by Similarity to Ideal Solution). This research focuses on the evaluation of various important criteria, such as performance (KPI), appearance, education level, work experience, and position, in determining more fair and objective compensation. The TOPSIS method is used to rank employees based on their proximity to the ideal solution. The results of the study show that the application of this method can result in a more transparent and objective evaluation compared to traditional methods. However, the main challenge faced is the difficulty in measuring non-quantitative criteria such as appearance. Therefore, further development of the system is needed in order to accommodate dynamic changes in criteria.